Concurrent involvement of bone and thyroid gland. Report of two cases of benign spinal lesion mimicking metastatic spine disease - Sharifudin, Mohd Ariff; Johari, Joehaimey; Omar, Ahmad Sabri; Zakaria@Mohamad, Zamzuri; Mohamed Amin, Mohamed Azril; Abd. Aziz, Azian (2014)
Introduction: The vertebra is the most frequent location for skeletal metastases. Thyroid carcinoma is one of the commonest primary sites that metastasized to the bone. Metastasis to the thoracic vertebra is commoner compared to lumbar and cervical areas. Clinical diagnoses are difficult when adult patients present with concurrent involvement of the thyroid gland and the thoracic vertebra. Methodology: We report two cases of adult presented with back pain in the thoracic region with profound neurological deficit. Both cases had involvement of the thyroid gland as well; the first patient had history of thyroid carcinoma and the other was an incidental finding. Clinically, their presentation mimicked the manifestation of metastatic spine disease. In both cases, two distinct diagnoses of benign bone lesions that are uncommon in adults were confirmed on histopathological evaluation. Results: The first case was a 53-year-old lady who presented with an 8-month history of pain in the thoracic region with paraparesis, which required assistance for ambulation. She had undergone total thyroidectomy for papillary thyroid carcinoma one year prior to her current problem. There was an isolated osteolytic lesion over the posterior element of T12 vertebra with narrowing of the spinal canal causing compression to the cord on MR imaging. CT-guided biopsy did not obtain any malignant cells. Posterior decompression with fusion and stabilization between T10 to L2 with pedicle screw system was performed. Posterior element of T12 and bilateral erector spinae muscles sent for histopathological evaluation and the diagnosis of fibrous dysplasia was made. Patient’s condition improved gradually until her recent follow up one year following her surgery. The second case is a 37-year-old man presenting with profound quadriparesis and incidental thyroid involvement. MR imaging and skeletal radiographs revealed widespread involvement of the spine. The patient underwent surgical resection of the tumour and stabilization of the spine. Diagnosis was confirmed by histological and immunohistochemistry analysis. Conclusion: These cases illustrate that osteolytic lesion of the vertebrae should be evaluated with detailed radiological and histopathological examination before an empirical diagnosis of spinal metastasis is made in adult patients presenting with features of metastatic spine disease.